2012
DOI: 10.2459/jcm.0b013e32834d21b4
|View full text |Cite
|
Sign up to set email alerts
|

Blood cyst of the mitral valve

Abstract: Blood cysts of the mitral valve are mostly benign diverticuli lined by endothelium and filled with blood and can be safely monitored with echocardiographic follow-up. We report a case of asymptomatic blood cyst of the mitral valve in a 63-year-old woman referred for a systolic murmur. At 3-year echo follow-up, the patient is free from notable clinical events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Our literature search has documented a total of 50 articles considered eligible for analysis and reporting a total of 54 patients; 36 (72%) are reports of a single case, 3–38 12 (24%) images in cardiovascular disease, 39–50 1 case series reporting 5 patients (2%), 51 and 1 letter to the editor (2%), 52 all published from 1960 to 2021 (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search has documented a total of 50 articles considered eligible for analysis and reporting a total of 54 patients; 36 (72%) are reports of a single case, 3–38 12 (24%) images in cardiovascular disease, 39–50 1 case series reporting 5 patients (2%), 51 and 1 letter to the editor (2%), 52 all published from 1960 to 2021 (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms related to the presence of MV BCs, in the absence of any other intracardiac abnormality, included predominantly palpitations, chest discomfort, and exertional dyspnea. In three patients, BCs caused severe left ventricular outflow tract (LVOT) obstruction, 5,11,50 two patients presented with hemiparesis, 4,43 two with syncopal episodes, 32,50 two had a stroke, 15,18 two a myocardial infarction, 9,21 and in one the BC caused severe MV regurgitation. 23 Except for the first two BCs cases described, diagnosed either by cineangiography 3 or M-mode echocardiogram, 5 in all other cases transthoracic 2D echo was used for evidencing the presence of an MV mass (Figure 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Researchers did not build any consensus on clinical management. Scattered studies have suggested conservative management for asymptomatic cases [ 7 ]. Since the hemodynamic implication of intracardiac blood cysts may cause dyspnea, chest pain, syncope, stroke, or even coronary artery embolism, surgical resection is warranted for symptomatic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our Literature search has documented a total of 50 articles considered eligible for analysis and reporting a total of 54 patients; 36 (72%) are reports of a single case , 12 (24%) images in cardiovascular disease [39][40][41][42][43][44][45][46][47][48][49][50] , 1 a case series reporting 5 patients (2%) 51 and 1 a letter to the Editor (2%) 52 , all published from 1960 to 2021 (Table 1 and 2…”
Section: Blood Cysts Of the Mitral Valvementioning
confidence: 99%